2021
DOI: 10.3390/su13020855
|View full text |Cite
|
Sign up to set email alerts
|

Project Portfolio Construction Using Extreme Value Theory

Abstract: Choosing proper projects has a great impact on organizational success. Firms have various factors for choosing projects based on their different objectives and strategies. The problem of optimization of projects’ risks and returns is among the most prevalent issues in project portfolio selection. In order to optimize and select proper projects, the amount of projects’ expected risks and returns must be evaluated correctly. Determining the relevant distribution is very important in achieving these expectations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…As emphasized by Refs. [ 39 , 69 ], this problem involves selecting the right risk measure for evaluating project portfolio risk during investment, requiring optimal modeling of risk correlations and uncertainties associated with inputs or calculations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As emphasized by Refs. [ 39 , 69 ], this problem involves selecting the right risk measure for evaluating project portfolio risk during investment, requiring optimal modeling of risk correlations and uncertainties associated with inputs or calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Research theme 2 – Risk Management as a Project Portfolio Management Process: It stems from the second cluster in the keywords co-occurrence network, centered around the keyword "Portfolio Management." As highlighted by [ [ 34 , 69 ]], it involves adopting an approach derived from Project Risk Management theory to analyze project portfolio risk. This second research theme is characterized by keywords such as Project Management, Risk Management, and Project Portfolio Risk, among others.…”
Section: Discussionmentioning
confidence: 99%
“…The conceptualization of risk derived from Modern Portfolio Theory, developed by Harry Markowitz in 1952, is presented as the seminal theory insofar as project portfolio risk is a concern [28]. Modern Portfolio Theory has been used to establish a parallel between financial portfolios and project portfolios, specifically focusing on risk incorporation into the project portfolio selection process [17,19], thus adopting a general risk management approach [20]. These studies are focused on the risk associated with financial results, generally defining the risk as a unidimensional measure.…”
Section: Literature Review 21 Risk In Project Portfoliosmentioning
confidence: 99%
“…In this regard, the risk is associated with variations in the portfolio's financial results due to the variation derived from each project and, by considering the correlation between each pair of projects. In other words, total portfolio risk can be considered to be composed of independent project risk and interdependent project risk [19].…”
Section: Literature Review 21 Risk In Project Portfoliosmentioning
confidence: 99%
“…In this regard, research has shown that the questionnaire survey is the most frequently used technique for risk identification in the construction sector [8,9]. However, despite the literature produced (see also [10][11][12][13][14]), few contributions (e.g., Tamošaitienė et al [12]) have been dedicated to the risks in Commercial and Recreational Complex Building Projects (CRCBPs)-which comprise shops connected to each other with sidewalks that are designed and built alongside recreational, residential, office, hotel, restaurant, and cinema spaces [15,16]. Among them, it is worth mentioning the work of Comu et al [17] that, despite classifying risks for CRCBPs, has the drawback of diverging from a very extensive list of risk factors (i.e., 21; much less than the 82 included in this study).…”
Section: Introductionmentioning
confidence: 99%